(untitled) (Neo Science Peer Reviewed Journal, 2023)
This article examines the development of the sawmilling and silk industries in the Republic of Uzbekistan, highlighting their significant contributions to the country’s economic growth and cultural heritage. The sawmilling industry has witnessed sustainable forest management practices, technological advancements, and value-added processing, leading to increased production capacity and diversified product offerings. Similarly, the silk industry has experienced improvements in sericulture practices, silk processing, and market promotion, revitalizing silk production and establishing Uzbekistan as a prominent silk producer. These developments have contributed to job creation, exports, and economic development, positioning Uzbekistan as a key player in these industries. The government’s focus on sustainability, technological innovation, and market expansion ensures a promising future for the sawmilling and silk industries in Uzbekistan.